Data collected in 2012 using Q-methodology to identify the importance of water-based ecosystem services derived from the Shoshone National Forest - Christopher A. Armatas (19657816) (2025)
This data publication contains the results of a 2012 study of the preferences of 96 stakeholders (e.g., farmers, ranchers, outfitters and guides, average citizens, natural resource managers and scientists, county commissioners) from Wyoming and Montana for 34 water-based ecosystem services. The ecosystem services were identified through literature review, focus groups, and pilot tests, and the list of services was considered to be a representation of the full range of water-based ecosystem services derived from the Shoshone National Forest in northwest Wyoming. Data include: (1) demographic data from each stakeholder (e.g., gender, age, education); (2) importance assigned to 34 water-based ecosystem services on a scale from ‘most important’ to ‘most unimportant’ and; (3) perceptions (i.e., qualitative data from short interviews) about the potential impact of various drivers on the flow of their two ‘most important’ ecosystem services. There is a wide range of goods and services being provided to humans by water resources (e.g. hydropower and recreation), but there is also a diversity of stakeholders that require or desire these benefits, also known as water-based ecosystem services, for everyday life. Land managers working for the USDA Forest Service in the semi-arid Rocky Mountain Region are tasked with the difficult job of managing scarce water resources in the face of competing human pressures and natural forces (e.g. climate change). Water management decisions on public lands can potentially impact the availability of a wide range of benefits derived from water to a wide range of stakeholders. This project aimed to inform policy-makers and land managers about the range of benefits people derive from water within and flowing from the Shoshone National Forest (SNF), and the importance of those water benefits to stakeholders in northwest Wyoming. Additionally, this project aimed to understand the perceptions of stakeholders regarding the threat of climate change, and other factors, to their ability to receive certain water-based ecosystem services.